Enhancing Animal Nutrition and Sustainability: The Vital Role of Genetically Modified Crops in Animal Feeding - Rukkiya Siddiqui; B.C. Mondal; Meesam Raza; Sawan Kumar; Rashmi Goswami; Muteeb Ullah Rafiqui; Adis Mirel Ahmed; Mohit Bhardwaj; Preeti Verma; Damini Arya (Archives of Current Research International, 2024)
Agriculture and livestock are fundamental to the economies of developing countries. A substantial portion of crop harvests is allocated for animal feed. Thus, more technological advancements are necessary to enhance agricultural productivity and provide affordable feed. Future biotech crops are expected to play a crucial role in this area. The goal is often to introduce traits into plants that do not naturally occur in these species. These new traits may include resistance to pests, diseases, or environmental conditions, or the production of specific nutrients or pharmaceutical agents. GM crops have indirectly benefited the livestock sector by increasing the yield of feed ingredients and improving quality traits. These crops are primarily used in livestock feed rations as energy and/or protein sources. Numerous animal feeding studies have been conducted to demonstrate that genetically modified crops are as nutritious and wholesome as compared to their conventional counterparts. No biological relevant differences in animal performance, health, or animal product (meat and milk) composition had been observed in various studies conducted. Overall, no significant differences in gain, intake, and feed conversion have been reported. Since the GM crop’s composition is not different from its conventional counterpart [except for the introduced transgene(s) and expressed protein(s)] and the expressed transgenic protein is rapidly digested in the digestive system, one would not expect any unintended effects. The introduction of genetically modified (GM) crops into the market undergoes extensive testing and a rigorous approval process to ensure food, feed, and environmental safety. This process includes thorough analyses before GM crops are deemed safe for commercial use. GM livestock feed is assessed for its nutritional composition and digestibility by comparing it with conventional crops. Therefore, while GM crops have the potential to enhance the efficiency of animal agriculture by improving nutritional content, reducing pesticide use, and increasing crop yields, it is essential to approach their adoption with caution.